A novel run-out model based on spatial tool position for micro-milling force prediction. (August 2021) - Jing, Xiubing; Lv, Rongyu; Song, Bowen; Xu, Jian; Jaffery, Syed Husain Imran; Li, Huaizhong
Abstract: The tool run-out significantly affects prediction of milling force, which is crucial for monitoring the micro-end-milling processes. For accurately predicting milling force, a novel tool run-out model is presented, which is based on spatial tool position to reflect a more realistic clamping situation. In the established model, the direction vector s ⃑ of the tool axis replacing the location angle ψ and tilt angle τ is firstly proposed to describe the tool position in space to simplify the calculation. The mechanistic cutting force model, which is relevant to instantaneous uncut chip thickness (IUCT), is adopted to predict milling force. An accurate IUCT at different axial positions is calculated by incorporating the proposed run out model on spatial tool position. The predicted cutting forces show a close agreement with the experimental cutting force. The proposed run-out model can be employed to identify the tool state as well as predict cutting force, thereof monitor the machining process. Graphical abstract: Unlabelled Image Highlights: A novel tool run-out model based on spatial tool position is presented to reflect a more realistic clamping situation. An accurate IUCT at different axial positions is calculated by incorporating the proposed run out model. An improved model is presented to rectify the effect of cutting parameters on tool runout and thereof on the cutting force. The proposed run-out model can be employed to identify the tool state as well as predict cutting force.